2010
DOI: 10.1007/s00277-010-0989-y
|View full text |Cite
|
Sign up to set email alerts
|

A new ankyrin mutation (ANK1 EXON E9X) causing severe hereditary spherocytosis in the neonatal period

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Abnormalities of protein 4.1R are much less common than spectrin mutations in the etiology of HE. Partial deficiency of protein 4.1R is associated with mild, dominant HE . In patients with severely dysfunctional spectrin mutations, the weakened spectrin dimer–dimer self‐association disrupts the skeletal lattice, leading to a marked skeletal instability and cell fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities of protein 4.1R are much less common than spectrin mutations in the etiology of HE. Partial deficiency of protein 4.1R is associated with mild, dominant HE . In patients with severely dysfunctional spectrin mutations, the weakened spectrin dimer–dimer self‐association disrupts the skeletal lattice, leading to a marked skeletal instability and cell fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic pattern of most HS patients with ANK1 mutations is autosomal dominant, but autosomal recessive inheritance has occurred in several such patients. Mutations in ANK1 are unique to an individual or an entire kindred [2, 10, 11], and common mutation sites in a family can be inherited. Miya et al [12] identified a 3.7-Mb deletion from 8p11.2 in a 19-month-old HS patient with Kallmann syndrome; the deleted region included ANK1 , but no mutation was found in any exons of ANK1 .…”
Section: Molecular Genetic Mechanisms Of Five Hs-related Genesmentioning
confidence: 99%
“…The research indicates that the sites related to HS gene mutation are mainly located in the following genes: ANKl, SPTB, SPTA1, EPB42, and SLC4A1. Among them, the most common type of mutation is ANK1 mutation, which accounts for about 50% of all HS gene mutation types (19)(20)(21), followed by SLC4Al and SPTB locus mutations (22,23).There are few related studies on HS gene in China, Most studies are case reports and lack of large sample studies (24)(25)(26). It is also rare research and large-scale studies on children's ANK1 gene in other countries (7).The 12 ANK1 mutation found in this study are all mutations unreported.…”
Section: Discussionmentioning
confidence: 99%